L-Tryptophan as Fluorescent Probe for Determination of Folic Acid in Some Pharmaceutical Products - Tahir, Tara F.; Qader, Aryan F.; Salih, Musher I.; Rashid, Essa Q. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
A new fluorescent probe L-Tryptophan was reported for the determination of folic acid (FA), based on its quenching effect of the fluorescence intensity of L-Tryptophan. The concentration of folic acid was proportional to the quenched fluorescence intensity of L-Tryptophan at an emission wavelength of 365 nm in Britton– Robinson (BR) buffer solution of pH 7. Optimized conditions of pH, time, order of addition of the reagent, potential interferences, concentrations of L-Tryptophan and buffer were investigated. Folic acid was determined in a linear range of 2.0 to 16.0 μg ml-1 with a correlation coefficient R2 0.9974. The limits of detection LOD and quantification LOQ values were 0.09 μg ml-1 and 0.27 μg ml-1, respectively. The standard deviation (RSD) values for five replicated measurements of 2, 8, 16 μg ml-1 folic acid were between 0.23 % and 1.07%. This method is efficient for routine analysis and quality control assay as it is relatively interferences free.